Androgen and Androgen Receptors as Regulators of Monocyte and Macrophage Biology in the Healthy and Diseased Lung - Becerra-Diaz, Mireya; Song, Mason; Heller, Nicola (Frontiers in Immunology, 2020)
Androgens are the male predominant male sex hormones, driving the development and maintenance of the male characteristics, by binding to androgen receptor (AR). Androgens, being systematically distributed to the whole organism, also exert functions in many other tissues and cell types in addition to those in male sexual organs. It is now clear that the immune system is a target of the action of androgens. In the lungs, many immune cells express AR and are responsive to androgens. In this review, we will focus on the effect of androgens and AR on the myeloid immune cells – monocytes and macrophages - in lung health and disease. Particularly, we will focus on the effect of androgens on lung diseases such as lung fibrosis, chronic obstructive pulmonary disease (COPD), and asthma. The therapeutic use of androgens and how circulating androgens correlate with lung disease will also be discussed. In addition to human studies, we will also discuss how mouse models have helped to uncover the effect of androgens on monocytes, macrophages, and dendritic cells in mouse models of lung disease. While the role for estrogen and other female hormones have been broadly analyzed in different reports, we will focus on the new perspectives of androgens as modulators of the immune system, targeting myeloid cells during lung inflammation.